2004
DOI: 10.1016/j.femsre.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends on the molecular biology of pneumococcal capsules, lytic enzymes, and bacteriophage

Abstract: Streptococcus pneumoniae has re-emerged as a major cause of morbidity and mortality throughout the world and its continuous increase in antimicrobial resistance is rapidly becoming a leading cause of concern for public health. This review is focussed on the analysis of recent insights on the study of capsular polysaccharide biosynthesis, and cell wall (murein) hydrolases, two fundamental pneumococcal virulence factors. Besides, we have also re-evaluated the molecular biology of the pneumococcal phage, their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 217 publications
(278 reference statements)
3
181
0
4
Order By: Relevance
“…Pneumococci can produce 13 to 16 different CBPs, including four cell wall hydrolases that are important for virulence: the major autolysin LytA (N-acetylmuramoyl-L-alanine amidase), a b-N-acetylglucosamidase (LytB), a b-N-acetylmuramidase (LytC; lysozyme), and a phosphorylcholine esterase. LytA has been characterized in detail, and recently the structural analysis of the CBD of LytA demonstrated that this module adopts a peculiar solenoid structure (Ló pez & García, 2004). LytB is highly expressed in the early exponential growth phase and has been shown to be important for cell separation of pneumococci.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…Pneumococci can produce 13 to 16 different CBPs, including four cell wall hydrolases that are important for virulence: the major autolysin LytA (N-acetylmuramoyl-L-alanine amidase), a b-N-acetylglucosamidase (LytB), a b-N-acetylmuramidase (LytC; lysozyme), and a phosphorylcholine esterase. LytA has been characterized in detail, and recently the structural analysis of the CBD of LytA demonstrated that this module adopts a peculiar solenoid structure (Ló pez & García, 2004). LytB is highly expressed in the early exponential growth phase and has been shown to be important for cell separation of pneumococci.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…Comparison of the primary structure of the deduced amino acid sequence of the BacL 1 protein showed significant homology with the cell wall lytic enzymes found in gram-positive bacteria (Fig. 4A) (32). Of the 595 amino acid residues of the BacL 1 protein, the N-terminal 151 amino acid residues showed a high level of homology with the lysozyme encoded on Bacillus subtilis bacteriophage B103 (accession number Q37896) (37).…”
Section: Cloning Of Component L Component a And The Immunity Genesmentioning
confidence: 86%
“…The deduced amino acid sequence encoded by bacL 1 showed a high degree of homology with the cell wall lytic enzymes and murein hydrolases of lysozyme, lysine, and the muramidase of gram-positive bacteria (32). These enzymes cleave glycan strains either between the N-acetylmuramic acid and N-acetylglucosamine or at the alternative acetylglucosamine-muramic acid glycoside linkage (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LytA, an N -acetylmuramyl-l-alanine amidase, is important for peptidoglycan remodeling during growth [36] and appears to be constitutively expressed [37,38]. Death or suicide of S. pneumoniae in the stationary phase has been attributed to autolysis by LytA [38,39], however, it has been proposed that spontaneous pneumococcal death is due to hydrogen peroxide (H 2 O 2 ), a by-product of aerobic metabolism by SpxB, not LytA [40]. Taken together, not only cell wall attached proteins but also exposed Ccs4 may interact with host cells when host-pneumococcal contact induces LytA expression, causing degradation of the cell wall peptidoglycan and capsule.…”
Section: Discussionmentioning
confidence: 99%